Bimetallic, Lewis acid and Brønsted acid catalysis in allylation and other organic transformations - Solic, Ivan (2019)
Allylic moiety, an important structural motif in organic chemistry, can be easily transformed into many different functionalities. Therefore, it is essential to develop new allylation methodologies. The first chapter will describe the use of scandium triflate as an efficient catalyst for the deoxygenative allylation of a variety of benzylic and benzyhydryl alcohols. An efficient and robust method for the formation of carbon-carbon bond has been developed. The mechanism of the reaction was studied as well and it was shown that the reaction actually proceeds through a “hidden Brønsted acid” mechanism. The second chapter will describe different reactions reported earlier in the literature. It is known that some Lewis acid-catalyzed and Brønsted acid-catalyzed reactions can be ambiguous, selected reactions were hence examined by addition of 2,6-di-tert-butyl-4-methylpyridine which is used to reveal the correct reaction pathway. In the third chapter, different secondary aromatic amines were synthesized and were employed in the bimetallic Pd/La catalyzed Tsuji-Trost type allylation. Underivatized allyl alcohols were used as allylating agents with lanthanum triflate as a water tolerant Lewis acid for hydroxyl activation. The bimetallic Tsuji-Trost type reaction was shown to be an efficient tool for allylation of a variety of nitrogen containing nucleophiles. Thus, it is a good methodology for the formation of the carbon-nitrogen bond. Investigation of the scope of the reactivity of nitrogen containing nucleophiles gave both expected and unexpected results. Nucleophiles with good activating groups have proved to be the best nucleophiles for this bimetallic Tsuji-Trost allylation. Nucleophiles with deactivating groups gave lower yields and require further optimization. Surprisingly, an aminopyridine proved to be an excellent substrate. The reaction also tolerated various substituent groups on the allylic alcohol.